Efisiensi usaha penangkapan gurita (octopus) Di Desa Tanomeha Kecamatan Kaledupa Selatan Kabupaten Wakatobi - Darsiah, Nurul; La Ola, La Onu; Mansyur, Akhmad; Sidiq, Azwar (Universitas Halu Oleo, 2024)
This study aims to examine the process of catching octopus, the amount of cost efficiency and the amount of profit in Tanomeha Village, Kaledupa District, Wakatobi Regency, Southeast Sulawesi, during the period March to April 2019. This study used a census method with 10 respondents. This research was obtained through observation and direct interviews using a questionnaire. Data were analyzed using descriptive analysis. Efficiency with the formula (E = TC/Q) and profit (Π = TR-TC). The results showed that the process of catching the octopus using a hand rod started when the fishermen went to the location to catch the octopus, when the hand line was lowered, it was jerked to attract the attention of the octopus to the movement of the bait. After the bait is caught, it is immediately withdrawn and lifted into the boat. The magnitude of the efficiency of fishing costs in the waters of Bungi is Rp. 13,367/kg and the efficiency of the costs of fishing in tinete waters is Rp. 31,799/kg. The amount of fishermen's profit in Bungi waters is IDR 193,347/trip and fishermen's profits in Tinete waters is IDR 8,988/trip